A Study on Planning and Application of Strategies Used for Menu Designing Of #x201C;SPICE ART#x201D; Restaurant (Global Journal of Management and Business Research, 2022)
This examination is completed in the viewpoint of continuous patterns in This study of Radisson Blu Greater Noida is based on the findings related to the practices of the front office department in the engagement of guest satisfaction activities. Customer satisfaction is a function of service performance in relation to customer expectations. As a result, it is critical to understand how customer expectations are formed in order to identify the factors that contribute to service satisfaction. Customer expectations are determined by their understanding of a product or service.
Keywords: customer preference; menu design; menu layout; customer satisfaction